(untitled) (World Journal of Current Medical and Pharmaceutical Research, 2019)
Alzheimer’s disease (AD) is the most common progressive neurodegenerative disease and the most common form of dementia. There are two major types of AD these are early onset Alzheimer’s disease (EOAD) and late onset Alzheimer’s disease (LOAD). The genetics of EOAD are largely understood with mutation in three different genes leading to the disease. Here we review the known genetics of EOAD. The most widely accepted hypothesis is the amyloid cascade hypothesis. Preliminary data suggest that CSF markers such as Aβ and Tau levels may be considered as a helpful tool in the diagnosis of early onset Alzheimer’s disease (EOAD). Assessment of biomarkers in EOAD should be recommended in order to increase diagnostic accuracy in those cases with atypical presentation and /or familial aggregation of the disease. The typical presentation is more frequent in EOAD than in late onset Alzheimer’s disease (LOAD). To date more than 160 highly penetrant but rare mutation have been described in three genes amyloid precursor protein(APP), presenilin 1(PSEN1) and presenilin 2(PSEN2). PSEN1 is the most frequently mutated EOAD gene with a mutation frequently of 18-50% in autosomal dominant EOAD.